Expertise and Power: Agencies Operating in Complex Environments - Zito, Anthony R. (2015)
This contribution investigates the strategies that environmental agencies develop to enhance their policy autonomy, in order to fulfil their organisational missions for protecting the environment. This article asks whether there are particular strategic moves that an agency can make to augment this policy autonomy in the face of the principals. Critiquing principal agent theory, it investigates the evolution of three environmental agencies (the European Environment Agency, the England and Wales Environment Agency and the United States Environmental Protection Agency), focusing on the case study of climate change. The contribution examines how the agencies influence environmental policy on domestic, regional and global levels, with a special focus on the principals that constrain agency autonomy. A greater focus on different multi-level contexts, which the three agencies face, may create other possible dynamics and opportunities for agency strategies. Agencies can use particular knowledge, network and alliance building to strengthen their policy/political positions.